Using and Building an Automatic Program Verifier (Lecture 2) - Leino, Rustan (Marktoberdorf Summer School 2011 Bayrischzell, BY, Germany, 2011)
Reasoning about programs Central to any programming task From safety critical applications to scripting From initial development to maintenance to debugging Minimizes faults, security problems, time/cost to market Thinking skill